THE EFFECTS OF LUPIN (Lupinus angustifolius) AS SOYBEAN SUBSTITUTE AND COAGULANT AGENT TO PROTEIN PRECIPITATION IN TOFU PREPARATION - Mery T.D Ambarita; Maria Stephanie; Yeti M. lskandar (Jurnal Kimia Terapan Indonesia, 2009)
Lupinus angustifolius is legume that has high protein. Most of this plant growth in Australia. Another name of L. angustifolius is Australian sweet lupin. L. angustifolius is potentially use as the source of food. Tofu is one of the traditional foods in Indonesia.Tofu is madefrom the coagulation of soybean protein. L. angustifolius has globulin protein that has a role in the production of tofu. The price of L. angustifolius is cheaper than soybean. In this research, L. angustifolius has beenused as the substitution in the tofu production. Thepurpose of this researchis toknow the nutrition and potential of L. angustifolius as the substitute in tofu. This research is also monitoring the effect of coagulant agent that is used in tofu. The research result shows that the optimum concentration substitution of lupin that is used in tofu is 30% with CaCl2 coagulant agent. The tofu that is made from 30% lupin with CaCl2 contained 17.22% protein, 5.23 fat, and 1.14% carbohydrate. The observation shows that tofu that is made from 30% substitution of L. angustifolius has higher protein than tofu which is without substitution of L. angustifolius.Keywords: Lupinus angustifolius, coagulant agent, tofu, protein.